(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
This article describes the stages of implementation of the integration of electronic educational resources to increase the efficiency of independent education of students of higher educational institutions and the results of research on determining the practical importance of integrating electronic educational resources